2022
DOI: 10.3389/fphy.2022.897255
|View full text |Cite
|
Sign up to set email alerts
|

Active Condensation of Filaments Under Spatial Confinement

Abstract: Living systems exhibit self-organization, a phenomenon that enables organisms to perform functions essential for life. The interior of living cells is a crowded environment in which the self-assembly of cytoskeletal networks is spatially constrained by membranes and organelles. Cytoskeletal filaments undergo active condensation in the presence of crosslinking motor proteins. In past studies, confinement has been shown to alter the morphology of active condensates. Here, we perform simulations to explore system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Interestingly, simulations have shown that the spatial confinement of actin facilitates symmetry breaking allowing for the formation of organised structures. In our system, the quasi-2D and 3D condensates initiate polymerization within the confined volumes of the condensates 62 . In conjunction with recent observations 35 , we believe that our findings experimentally demonstrate that the confined polymerization of actin within LPD 850-1250 -VASP condensates is an example of a series of symmetry breaking events (Fig 7).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, simulations have shown that the spatial confinement of actin facilitates symmetry breaking allowing for the formation of organised structures. In our system, the quasi-2D and 3D condensates initiate polymerization within the confined volumes of the condensates 62 . In conjunction with recent observations 35 , we believe that our findings experimentally demonstrate that the confined polymerization of actin within LPD 850-1250 -VASP condensates is an example of a series of symmetry breaking events (Fig 7).…”
Section: Discussionmentioning
confidence: 97%
“…Ring morphologies have been observed in micron sized contractile rings 68 and nano-scale structures at the base of endocytic buds [69][70][71] . Interestingly, simulations and experiments have shown that the spatial confinement of actin facilitates symmetry breaking, allowing for the formation of organised structures 72,73 . In our system, actin polymerization is initiated within the confined volumes of quasi-2D and 3D condensates, suggesting a possible role for symmetry breaking.…”
Section: Discussionmentioning
confidence: 99%
“…In plant cells, the cell wall provides rigid external confinement, and the large vacuole can occupy up to 90% of the cytoplasm, leading to quasi-2D environments between the vacuole and plasma membrane (42). Recent experimental and computational studies have demonstrated that confinement impacts the organization of motor-filament systems, promoting the formation of polar and nematic flows (43)(44)(45), as well as aster-like structures (22).…”
Section: Introductionmentioning
confidence: 99%
“…Sorting by filament polarity has been associated with polar flows, vortices, and asters in kinesin-microtubule systems (18, 19) and asters in myosin II-actin systems (20, 21). Polarity sorting in these systems has been attributed to the end-dwelling nature of kinesins and myosin II (20, 22). Recently, Memarian et al (23) studied microtubules propelled by membrane-bound kinesin motors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation